2017
DOI: 10.1083/jcb.201606082
|View full text |Cite
|
Sign up to set email alerts
|

A STRIPAK complex mediates axonal transport of autophagosomes and dense core vesicles through PP2A regulation

Abstract: The regulation of cargo transport within neurons is not well understood. Neisch et al. use Drosophila genetics to identify a multiprotein STRIPAK complex required for autophagosome and dense core vesicle transport in neurons. PP2A activity within the complex is necessary for transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 94 publications
3
84
0
1
Order By: Relevance
“…In this role, PP2A in the STRIPAK deactivates Hippo kinases, which in turn leads to decreased Warts/LATS kinase activation. Notably, fly Mob4 and the STRIPAK complex are required for normal formation of synaptic boutons at fly neuromuscular junctions, a process regulated by Tricornered and Mob2 (Schulte et al, 2010;Neisch et al, 2017).…”
Section: The Stripak Complex Is a Negative Regulator Of Hippo Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this role, PP2A in the STRIPAK deactivates Hippo kinases, which in turn leads to decreased Warts/LATS kinase activation. Notably, fly Mob4 and the STRIPAK complex are required for normal formation of synaptic boutons at fly neuromuscular junctions, a process regulated by Tricornered and Mob2 (Schulte et al, 2010;Neisch et al, 2017).…”
Section: The Stripak Complex Is a Negative Regulator Of Hippo Signalingmentioning
confidence: 99%
“…The roles of other STRIPAK components are less understood. An intact STRIPAK complex is required for negative regulation of Hippo signaling in distinct Drosophila cellular contexts, but the contribution of Mob4/Phocein has yet to be defined (Ribeiro et al, 2010;Schulte et al, 2010;Sakuma et al, 2016;Zheng et al, 2017;Neisch et al, 2017;Gil-Ranedo et al, 2019). Mob4/Phocein proteins have been shown to bind directly to STE20 kinases in both fly and mammalian cells (Ribeiro et al, 2010;Couzens et al, 2017;Chen et al, 2018), but it is unclear if Mob4/Phocein is required to recruit GCK-type STE20 kinases to the STRIPAK complex.…”
Section: The Stripak Complex Is a Negative Regulator Of Hippo Signalingmentioning
confidence: 99%
“…As ribbon synapses mediate transmission between IHCs and spiral ganglion neurons (SGNs), our results lead us to propose that striatin, a component of the STRIPAK complex that interacts with the tumor supressor protein APC, regulates interneuronal synapses. This finding is supported by the observation that the Drosophila striatin homolog, CKA, facilitates axonal transport of dense core vesicles and autophagosomes in a PP2A-dependent manner [34].…”
Section: Striatin Knockout Mice Display An Aberrant Ribbon Gradientmentioning
confidence: 67%
“…Unlike hippocampal or cortical neurons, which are typically isolated from embryonic or early postnatal rodents, DRG neurons can be isolated from mice of any age and grow robustly in culture following dissection. Importantly, the spatial enrichment of autophagosome biogenesis in the distal neurite observed in culture (Maday and Holzbaur, 2014;Maday et al, 2012) has been confirmed in C. elegans and Drosophila neurons in vivo (Neisch et al, 2017;Stavoe et al, 2016). Since impaired autophagy has been implicated in the pathogenesis of neurodegenerative diseases and age is the most relevant risk factor for neurodegenerative disease, we examined how autophagosome biogenesis rates change with age.…”
Section: Autophagosome Biogenesis At the Axon Terminal Of Neurites Dementioning
confidence: 85%